Unlocking New Reactivities in Enzymes by Iminium Catalysis. (15th June 2022) - Xu, Guangcai; Poelarends, Gerrit J.
Abstract: The application of biocatalysis in conquering challenging synthesis requires the constant input of new enzymes. Developing novel biocatalysts by absorbing catalysis modes from synthetic chemistry has yielded fruitful new‐to‐nature enzymes. Organocatalysis was originally bio‐inspired and has become the third pillar of asymmetric catalysis. Transferring organocatalytic reactions back to enzyme platforms is a promising approach for biocatalyst creation. Herein, we summarize recent developments in the design of novel biocatalysts that adopt iminium catalysis, a fundamental branch in organocatalysis. By repurposing existing enzymes or constructing artificial enzymes, various biocatalysts for iminium catalysis have been created and optimized via protein engineering to promote valuable abiological transformations. Recent advances in iminium biocatalysis illustrate the power of combining chemomimetic biocatalyst design and directed evolution to generate useful new‐to‐nature enzymes. Abstract : This Minireview summarizes the different strategies used in the design and engineering of novel enzymes that accommodate iminium catalysis. The advantages and challenges of developing enzymes for this catalysis mode are discussed. Recent developments in iminium biocatalysis showcase the tremendous power of combining chemomimetic biocatalyst design and directed evolution to create useful biocatalysts for new‐to‐nature transformations.